The FgSRP1 SR‐protein gene is important for plant infection and pre‐mRNA processing in Fusarium graminearum. (3rd August 2017) - Zhang, Yimei; Gao, Xuli; Sun, Manli; Liu, Huiquan; Xu, Jin‐Rong
Summary: The versatile functions of SR (serine/arginine‐rich) proteins in pre‐mRNA splicing and processing are modulated by reversible phosphorylation. Previous studies showed that FgPrp4, the only protein kinase among spliceosome components, is important for intron splicing and the FgSrp1 SR protein is phosphorylated at five conserved sites in Fusarium graminearum . In this study, we showed that the Fgsrp1 deletion mutant rarely produced conidia and caused only limited symptoms on wheat heads and corn silks. Deletion of FgSRP1 also reduced ascospore ejection and deoxynivalenol (DON) production. Interestingly, FgSRP1 had two transcript isoforms due to alternative splicing and both of them were required for its normal functions in growth and DON biosynthesis. FgSrp1 localized to the nucleus and interacted with FgPrp4 in vivo . Deletion of all four conserved phosphorylation sites but not individual ones affected the FgSRP1 function, suggesting their overlapping functions. RNA‐seq analysis showed that the expression of over thousands of genes and splicing efficiency in over 140 introns were affected. Taken together, FgSRP1 is important for conidiation, and pathogenesis and alternative splicing is important for its normal functions. The FgSrp1 SR protein is likely important for pre‐mRNA processing or splicing of various genes in different developmental and infection processes.